A trail on the water: Abbado - Nono - Pollini - Ehrhardt, Bettina (Munich bce film, 2001)
This 2001 documentary offers a portrait of Venetian composer Luigi Nono (1924-1991), through the eyes of two musicians who forged a close personal and musical relationship with him: Claudio Abbado and Maurizio Pollini. Nono's widow and André Richard, who engineered the live electronics of one of the works featured here, Prometeo, are also interviewed.The documentary provides revealing insights into a composer whose works were rarely performed in Italy, partly as a result of his strong communist but anti-fascist beliefs. Abbado and Pollini describe the philosophy shared by all three musicians and the influences they have had on each other.The film by Bettina Ehrhardt is centred around two of Nono's key works: his piano work Sofferte onde serene and the suite from his later orchestral work Prometeo, performed here in rehearsal by the Berlin Philharmonic and Claudio Abbado. Scenes and impressions of Venice accompany the music.